TRANSLATION SHIFT IN JAVANESE SHORT MOVIES SUBTITLE - Nasution, Ailman Rani; Hasibuan, Juli Rachmadani (TRANSFORM: Journal of English Language Teaching and Learning, 2020)
Translation Shift In Javanese Short Movies Subtitle was the subject of this research. The aimed of this study was to characterize the category shift that happened in Javanese short movies that were transcripted. It also attempted to describe the reasons for using category shifts, as well as the effects of those category shifts on transmitting SL signals. This study employed a descriptive qualitative approach, with the research data analyzing the prevalence of category shifts in the subtitles of short movies, where the writer chose the subtitles at random. The writer entered the information into a table and then compared the subtitles of two short movies from the SL to the TL. According to the conclusions of this study, there were four types of shifts: structure shift, unit shift, class shift, and intra-system shift. The largest category shift was on unit shift, which included 11 out of the total 15 sentences, or 36,6% of the instances, the other side of the lowest category shift found was class shift just had 3 cases out of 30 cases wich is had 10%, structure shift and intrasystem shift had the similarities between their result, which were had 8 cases each other or had 26,7% of the percentage.